2013
DOI: 10.1159/000350470
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interleukin-6 on the Expression of Tight Junction Proteins in Isolated Cerebral Microvessels from Yearling and Adult Sheep

Abstract: Objectives: The blood-brain barrier is a selective diffusion barrier between brain parenchyma and the intravascular compartment. Tight junctions are integral components of the blood-brain barrier. Pro-inflammatory cytokines are important in the pathogenesis of brain injury and could modify the protein constituents of tight junctions. We hypothesized that interleukin-6 (IL-6) downregulates key protein constituents of endothelial tight junctions (e.g. occludin and claudin-5). Methods: We examined the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 38 publications
5
43
0
Order By: Relevance
“…Blocking IL-6 signaling removed the stimulatory effect of A4 cell exposure to NMO-IgG, whereas inducing IL-6 signaling in ECs was sufficient to mediate downstream consequences of abluminal NMO-IgG for astrocyte/EC co-cultures. These observations are consistent with reports that astrocytes express IL-6 in neuroinflammation 26 and that IL-6 downregulates EC tight junction molecules, 27 decreases barrier function, 28,29 and induces CCL2 and CXCL8. 30,31 In vitro, increased barrier permeability and enhanced leukocyte migration can also be induced via complement-dependent astrocytopathy, a mechanism associated with destructive lytic lesions in patients.…”
Section: Discussionsupporting
confidence: 93%
“…Blocking IL-6 signaling removed the stimulatory effect of A4 cell exposure to NMO-IgG, whereas inducing IL-6 signaling in ECs was sufficient to mediate downstream consequences of abluminal NMO-IgG for astrocyte/EC co-cultures. These observations are consistent with reports that astrocytes express IL-6 in neuroinflammation 26 and that IL-6 downregulates EC tight junction molecules, 27 decreases barrier function, 28,29 and induces CCL2 and CXCL8. 30,31 In vitro, increased barrier permeability and enhanced leukocyte migration can also be induced via complement-dependent astrocytopathy, a mechanism associated with destructive lytic lesions in patients.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Cohen et al have demonstrated the ability of IL-6 to decrease occludin and claudin-5 expression in ovine cerebral microvessels ex vivo [31], whilst a role for TNF-α in BBB permeabilization in an in vivo mouse model has recently been reported by Wilson et al [32]. In contrast to our findings however, the aforementioned study by Cohen et al demonstrated that IL-6 concentrations below 100 ng/ml did not reduce protein expression, whilst 10 ng/ml of IL-6 was actually seen to increase claudin-5 expression in cerebral microvessels from yearling sheep [31]. In other contrasting studies, a lack of effect on VE-cadherin expression has been reported for hCMEC/D3 cells treated with similar concentrations of TNF-α [30], whilst a recent study by Aveleira et al demonstrates significant upregulation of occludin protein expression in bovine retinal microvascular endothelial cells following TNF-α treatment [11].…”
Section: Discussionmentioning
confidence: 83%
“…3&4). Other in vitro studies have also shown pro-inflammatory cytokines to increase endothelial and epithelial cell monolayer permeability (Desai et al, 2002; Capaldo and Nusrat, 2009; Cohen et al, 2013). TNF-α impairs the role of tight junction proteins in a number of cell types including human umbilical vascular endothelial cells (HUVEC) and human colonic adenocarcinoma (Caco-2) cells.…”
Section: Discussionmentioning
confidence: 94%